The The Relationship Between Nurses' Response Time and Patient Satisfaction in the Emergency Department of a Private Hospital in Surabaya, Indonesia - Widayani Yuliana; Siti Zulichah (Universitas STRADA Indonesia, 2026)
A fast response time in providing care will improve patient satisfaction levels. However, overcrowding in the Emergency Department (ED) often prevents nurses from delivering optimal care, resulting in 60% of patients reporting dissatisfaction and only 40% expressing satisfaction. This study aimed to analyze the relationship between nurses’ response time and patient satisfaction levels in the Emergency Department. This study employed a correlational analytic design with a cross-sectional approach. The population consisted of hospitalized yellow-triage patients admitted through the Emergency Department of a private hospital. A total of 78 respondents were selected using a consecutive sampling technique.The results showed that 78% of respondents received rapid response-time services, while 81% reported being very satisfied with the nursing care provided. Statistical analysis using the Spearman Rank test demonstrated a significant relationship between nurses’ response time and patient satisfaction (p = 0.002 < α = 0.05), with a correlation coefficient of r = 0.345, indicating a weak positive correlation. This finding suggests that faster nurse response times are associated with higher patient satisfaction levels. A fast response time plays an important role in determining patient satisfaction. Therefore, it is necessary to improve nurses’ skills, attitudes, and knowledge through continuous training programs to enhance the quality of emergency care services and ensure timely and accurate patient management in the Emergency Department.